ANALISIS KOMPENSASI BERBASIS JOB VALUE PADA UKM COFFEE SHOP XYZ DI KOTA DEPOK - Ratna Nurlita; Nada Farhanah; Syarah Trie Rachmawati; Nadila Nur’Aeni; Irnadia Fardila; Lindawati Kartika (Jurnal Pijar, 2023)
Human resources with enough competence and high motivation are necessary to improve the performance of SMEs. Compensation is one factor that influences competence and motivation. Compensation is a type of appreciation intended to provide feedback on the job performed by employees for a company, both financial and non-financial. As a result, SMEs require effective compensation management to boost employee competency and motivation. This study was carried out at the XYZ coffee shop in Depok with the goal of examining and enhancing the compensation management system at the XYZ coffee shop. This study's sample is the overall employee salary data for UKM Coffee shop XYZ, which has a total of 20 employees. Data collection techniques used are census techniques (non-probability sampling) and purposive sampling. This study employs descriptive statistical analytic methodologies, pay mapping, and point-based job values. According to the findings of this study, the XYZ coffee shop's financial compensation management system is not appropriate. The findings of the researchers' evaluation can be utilised by the management of the XYZ coffee shop to develop a more effective and optimum remuneration system. Keywords: Compensation, Job Value, Salary Mapping, Point System